The identities of three species of Parahelice Sakai, Türkay & Yang, 2006 (Crustacea: Brachyura: Varunidae) from the western Pacific, based on morphological and molecular evidence - Shih, Hsi-Te; Hsu, Jhih-Wei; Li, Jheng-Jhang; Ng, Ngan Kee; Lee, Jung-Hsiang (Zootaxa, 2020)
Species of the varunid genus Parahelice Sakai, Türkay & Yang, 2006, inhabit high intertidal areas of oceanic islands of the tropical Indo-West Pacific region. As several species of Parahelice and Pseudohelice subquadrata (Dana, 1851) were found to be sympatric in some places, and their morphological differences are minor, especially in females, the misidentification of species is not uncommon in the literature. In this study, the DNA barcoding marker, mitochondrial cytochrome c oxidase subunit I (COI), was applied to confirm species identities and this was correlated with the specific characters of males and females. Distributions of three species of Parahelice were also updated, with Par. daviei (Sakai, Türkay & Yang, 2006), Par. pilimana (A. Milne-Edwards, 1873), and Par. pilosa (Sakai, Türkay & Yang, 2006) being new records to Taiwan, and Par. pilosa new to Bali, Indonesia.